Correlation Between Bilingualism and Pronunciation: A Study of Seventh Grade Junior High School Students - Zulkiflih, Reza; Arafiq, Arafiq; Isnaeni, Muh (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to examine the correlation between bilingualism and English pronunciation skills of seventh-grade students at SMPN 21 Mataram. The subjects were 32 students, including 20 bilingual students proficient in both Indonesian and English. Primary data were collected through pronunciation tests at the word, phrase, and sentence levels, while secondary data included students’ demographic information. Quantitative analysis was performed using descriptive statistics, including mean, median, mode, range, and percentage of pronunciation performance. The results indicate that students’ overall pronunciation ability is in the fair category, with bilingual students generally achieving higher scores: 55% for word-level, 62% for phrase-level (stress and linking), and 59% for sentence-level (fluency and intonation). These findings suggest that students’ first language influences their pronunciation, causing certain errors to persist. This study provides an overview of pronunciation skills and bilingual usage in the classroom and offers a foundation for further research and the development of more effective English teaching strategies.